JAK Inhibitor and Crohn’s Disease - Mengyan Xu; Shi Wang; Sanping Xu; Rui Gong (Biomedicines)
Crohn’s disease is a chronic inflammatory granulomatous disease of the gastrointestinal tract. The global incidence and prevalence of Crohn’s disease have significantly increased, largely due to genetic susceptibility, environmental changes, and advancements in diagnostic technology. In recent years, the pharmacologic treatment of Crohn’s disease has been rapidly changing, and although biologics have improved the prognosis of patients to a certain extent, they still have certain limitations. Oral small molecule drugs like JAK inhibitors have become a research hotspot because of their advantages of targeting and regulating the JAK/STAT pathway, convenient administration, and rapid onset of action. JAK inhibitors exhibit divergent therapeutic profiles. Clinical trials have shown that tofacitinib demonstrates limited efficacy in Crohn’s disease management. Filgotinib initially showed clinical remission in phase 2 trials; while its subsequent phase 3 studies failed to demonstrate consistent endoscopic improvement. In contrast, upadacitinib achieved notable clinical remission rates during both induction and maintenance phases of phase 2 trials. However, long-term safety concerns, including thromboembolic events, cardiovascular events, opportunistic infections, and potential malignancy risks, warrant cautious clinical application. This article systematically reviews the pathophysiology of Crohn’s disease, and the evidence for the efficacy and safety of JAK inhibitors to guide clinical practice and research.